Auf offener Strasse. - Bauer, Stéphane; Kunstraum Kreuzberg/Bethanien, Berlin (Berlin : Kunstraum Kreuzberg/Bethanien Berlin, 2001)
Arlt, Peter ; Driesch, Roswitha von den ; Dyffort, Jens-Uwe ; Ebenhofer, Walter ; Eckelt, Roland ; Faust, Jeanne ; Grösch, Wiebke ; Harms, Imma ; Hasucha, Christian ; Hopf, Judith ; Koch, Andreas ; Lockemann, Ingeborg ; Marhöfer, Elke ; Mauss, Jan-Holger ; Metzger, Frank ; Micheel, Stefan ; p.t.t.red ; ready made berlin ; Schweiger, Michaela ; Sebestyén, Nada ; Sidow, Nina ; Winkelkotte, Thomas ; Zufferey, Christine
Duits
Auf offener Strasse, Kunstraum Kreuzberg/Bethanien Berlin, 27. Oktober bis 16. Dezember 2001
kunstcatalogus